The Pop Music Idol and the Spirit of Charisma - Cvetkovski, T. author. aut Link
XIII, 225 p.
Keywords: This book makes a case for the synergetic union between reality TV and the music industry. It delves into technological change in popular music, and the role of music reality TV and social media in the pop production process. It challenges the current scholarship which does not adequately distinguish the economic significance of these developments.